Student-Centered Classroom Management: Transforming the Teacher’s Role from Knowledge Transmitter to Values Facilitator within the Kurikulum Merdeka Ecosystem - Widianti; Abdillah Shafrianto; Nawan Kuban; Shopiyatul Khoiriyah; Suci Wiranti; Wanda; Lidya (Edumaspul: Jurnal Pendidikan, 2025)
The implementation of Kurikulum Merdeka in Indonesia necessitates a fundamental shift in classroom management from teacher-centered knowledge transmission to student-centered value facilitation. This study examines how teachers transform their roles from transmitters of knowledge into facilitators of values within the Kurikulum Merdeka framework. Employing a narrative literature review approach, data were collected from peer-reviewed journal articles and credible educational reports indexed in Google Scholar, published between 2019 and 2024. Thematic analysis revealed three key findings: (1) the transformation of physical and psychological classroom environments through flexible seating arrangements and co-constructed classroom agreements; (2) the shift from instructional monologues to dialogic and reflective teacher-student interactions, including emotional check-ins; and (3) the integration of value facilitation practices through differentiated instruction and formative assessment aligned with the Profil Pelajar Pancasila. However, challenges such as role confusion, fear of losing control, and administrative overload persist. The study concludes that successful transformation requires sustained systemic support, including targeted professional development, instructional leadership, and active professional learning communities. These findings offer practical insights for educators, school leaders, and policymakers seeking to bridge the gap between curriculum policy and classroom reality.